Reliability of Eelectromyography of Abdominal Muscles During Abdominal Manoeuvre with and without Pelvic Floor Muscle Contraction - Motahareh Hashem-Boroujerdi; Amir Masoud A'rab; Nouroddin Karimi; Nahid Tahan (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The purpose of this study was to determine the reliability of electromyography measurements of abdominal muscles activity during different manoeuvres (pelvic floor muscle (PFM) contraction, abdominal hollowing and abdominal bracing with and without PFM contraction) in subjects with and without chronic low back pain (LBP). Materials & Methods: In this methodology research 21 subjects (9 with LBP, 12 without LBP) who were selected simply & conveniently participated in the study. Abdominal muscle activation amplitude was assessed. Each maneuver was performed in triplicate and repeating of the test was done on the same day with a period of at least 30 minutes. Data were analyzed by Kolmogroff-Smirnoff test and Interclass correlation coefficient. Results: The results showed high reliability for the muscle activation amplitude during abdominal hollowing with and without pelvic floor muscle contraction and isolation pelvic floor muscle contraction and abdominal bracing (ICC=80-90). Also moderate reliability in abdominal bracing with pelvic floor muscle contraction (ICC=70-80).   Conclusion: Electromyography is a reliable method for assessment of voluntary and automatic activity of abdominal muscles during different conditions.